Pengaruh Pola Asuh Orang Tua terhadap Screen Time pada Anak Usia Dini (di RA Al-Abror Kecamatan Kersamanah Kabupaten Garut) - Sriastuti, Widi (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2025)
The phenomenon of screen time among early childhood populations has emerged as a critical issue in the digital era, given its significant impact on children's social, emotional, and cognitive development. This study aims to examine the influence of authoritarian, democratic, and permissive parenting styles on the duration of digital device use among young children. A quantitative approach with a causal-comparative design was employed, involving 30 parents of children aged 3–6 years at RA Al-Abror, Kersamanah District, Garut Regency, selected through purposive sampling. Data were collected using a validated and reliable questionnaire and analyzed through simple regression. The results indicate that all three parenting styles significantly affect screen time duration. Democratic parenting tends to reduce the time children spend on digital media, while both authoritarian and permissive styles are positively correlated with increased screen time. These findings align with Santrock's theory, which suggests that democratic parenting supports the development of adaptive behavior in children. The study concludes that adopting appropriate parenting styles is essential for managing children's screen time in a healthy and balanced manner to prevent the adverse effects of excessive digital exposure. Theoretically, the findings enrich the literature on the relationship between parenting styles and children's digital habits, while practically serving as a reference for parents and educators in implementing wise parenting strategies. This study also opens avenues for further research on parenting and the potential for digital addiction in early childhood.